The Benefits of Meditation for Reducing Perceived Anxiety in College Students: A Literature Review - Ava Pappas (Undergraduate Research Journal for the Human Sciences, 2025)
Anxiety is the most prevalent mental health issue in college students, affecting the mental, emotional, and physical aspects of daily life. There is a rising demand for mental health services, which has caused conventional treatments like therapy and medication to be spread thin. Complementary and alternative approaches have gained traction due to being cost-effective and easy. This literature review examines the effects of meditation on anxiety levels in college students based on findings from peer-reviewed studies. Evidence from multiple intervention studies exhibit notable reductions in perceived anxiety among college students who practice meditation of various forms. Furthermore, meditation benefits additional facets of well-being, like enhancing emotional regulation, mindfulness, and overall mental health. Despite certain limitations, such as reliance on self-reported data and insufficient long-term follow-ups, the results are consistent in highlighting the viable benefits of meditation. The findings postulate meditation as a tool for reducing anxiety and enhancing well-being in the college population. Further investigation should research long-term effects and the realistic integration of meditation into college student initiatives.
Keywords: Meditation; Anxiety; College Students; Mindfulness; Emotional Regulation